Ontological Freedom in Jan Patočka’s “Natural World as a Philosophical Problem” with Regard to Husserl’s Phenomenology - Rybák, David (Forum Pedagogiczne, 2019)
In his post-doctoral dissertation Přirozený svět jako filosofický problém (The Natural World as a Philosophical Problem; orig. publ. 1936) Jan Patočka critically deals with modern metaphysics of subjectivity, at the same time introducing phenomenology with its phenomenological reduction. I would like to investigate this issue in the text just mentioned and briefly compare the similarities and differences in Edmund Husserl’s phenomenology. Patočka provides a deepening of phenomenology by approaching the ontological conditions for the phenomenological reduction in the negativity of freedom in which the spontaneity of ‘having-the-world’ originates.